Bleed For Me - Robotham, Michael (Shere, 2010)
"Psychologist Joe O'Loughlin is being pushed away. His marriage is ending. Charlie, his eldest daughter, will barely speak to him. And Charlie's rebellious best friend Sienna is getting into more and more trouble, and taking Charlie along for the ride. Sienna has been almost like family to O'Loughlin-a troubled child who for years spent more time in the O'Loghlin residence than her own home. O'Loughlin's worst fears are confirmed when Sienna turns up at his front door, traumatized and covered in blood. The police find a major piece of the puzzle at Sienna's house: her father Ray Hegarty, a celebrated former police officer, murdered. The blood covering Sienna was her father's. She can't remember what happened, but, at the same time, doesn't mourn her father's death. O'Loughlin vows to unearth the dark secrets of Sienna's mind, hoping his efforts will win back the confidence of a daughter he may be in danger of losing forever. But as the accusations fly, the line between victim and accused begins to blur. When the detective in charge of the case seems all too eager to lay the blame at Sienna's feet rather than malign the honor of a respected former colleague, O'Loughlin begins to make his own inquiries. But each step he takes toward the truth also brings him closer to the path of a manipulative killer unlike anything he has ever encountered"--